Matrix-assisted laser desorption/ionization analysis of the brain proteome of microgravity-exposed mice from the International Space Station - Vigil, Correy; Daubenspeck, April; Coia, Heidi; Smith, Jerremy; Mauzy, Camilla (Frontiers in Space Technologies, 2022)
Manned spaceflight exposes humans to extreme environmental conditions, including microgravity exposures. The effects of microgravity during spaceflight could lead to changes in brain structure, gene expression, and vascular physiology. Given the known physiological effects, it is highly likely that there are microgravity-initiated proteomic differentials in the brain, possibly domain specific. MALDI-TOF (matrix-assisted laser desorption/ionization time of flight) Imaging Mass Spectrometry allows the visualization of the spatial distribution of highly abundant intact proteins in tissue specimens. This study utilized this technique to visualize global proteomic changes induced by microgravity exposure in brain tissue received from the Rodent Research-1 Center for the Advancement of Science in Space (CASIS)/National Aeronautics and Space Administration (NASA). Proteome profiles were obtained from isolated whole brain tissue from microgravity exposed, Habitat control, and baseline. While a total of 135 mass peaks equating to individual proteins were identified, statistical analysis determined that there were no significant differences in the spectra profiles from the three test groups utilizing this methodology, possibly due to sample collection logistics rather than lack of cellular response.